RADT-13. SPARE TRIAL: SCALP-SPARING RADIATION WITH CONCURRENT TEMOZOLOMIDE AND TUMOR TREATING FIELDS FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (12th November 2021) - Miller, Ryan; Song, Andrew; Ali, Ayesha S; Bar-Ad, Voichita; Martinez, Nina, L; Glass, Jon; Alnahhas, Iyad; Andrews, David; Judy, Kevin; Evans, James; Farrell, Christopher; Werner-Wasik, Maria; et al.
Abstract: INTRODUCTION: Current adjuvant treatment for patients with newly diagnosed glioblastoma includes concurrent chemoradiation and maintenance temozolomide with Tumor Treating Fields (TTFields). We report our clinical trial evaluating feasibility and tolerability of scalp-sparing radiation with concurrent temozolomide and TTFields. METHODS: Adult patients (age ≥ 18 years) with newly diagnosed glioblastoma with a KPS of ≥ 60 were eligible. All patients received concurrent scalp-sparing radiation (60 Gy in 30 fractions) with temozolomide (75 mg/m 2 daily) and TTFields (200 kHz). Maintenance therapy included temozolomide and continuation of TTFields. Radiation treatment was delivered through TTFields arrays. The primary endpoint was safety and toxicity of tri-modality treatment within 30 days of completion of chemoradiation treatment. RESULTS: Thirty patients were enrolled. Twenty were male and ten were female, with a median age of 58 years (range 19 to 77 years). Median follow-up was 10.8 months (range 1.6 to 21.3 months). Twenty (66.7%) patients had unmethylated MGMT promotor and ten (33.3%) patients had methylated promoter. Scalp dose constraints were achieved for all patients. Skin adverse events (erythema, dermatitis, irritation, folliculitis) were noted in 83.3% of patients, however, these were limited to Grade 1 or 2 events, which resolved spontaneously or with topical medications. No patient had radiation treatment interruption due to skin AEs. Other Grade 1 events included pruritus (33.3%), fatigue (30%), nausea (13.3%), headache (10%), dizziness (6.7%), and cognitive impairment (3.3%). Other Grade 2 events included headache (3.3%). The median PFS for the entire cohort was 9.1 months (at least 8.5 months, 95% confidence). The median PFS for patients with MGMT promoter methylation status was 11.4 months (at least 9.5 months, 95% confidence). Overall survival was not reached. CONCLUSIONS: Concurrent TTFields with scalp-sparing chemoradiation is feasible treatment option with limited toxicity. Future randomized prospective trials are warranted to define therapeutic advantages of concurrent TTFields with chemoradiation.